Durability in male professional road cyclists - Spragg, James (Department of Human Biology, 2026)
The aim of this thesis was to investigate the phenomenon of durability in male professional road cyclists. Durability can be described as the ability to resist a fatigue-induced downward shift in the power duration relationship. Prior to this thesis, this phenomenon had been identified within the literature, however, it had not been systematically studied. Therefore, the primary aims of this thesis were to i) Synthesis the current research concerning durability and the fatigue-induced downward shift in the power duration relationship ii) Investigate whether methodological artefacts in the hitherto research were influencing the current understanding of durability iii) Assess whether durability is trainable and which modalities of training may be beneficial to improve durability iv) Investigate if the intensity of prior work influences durability and v) to investigate the potential underlying physiological determinants of durability. The final goal was to summarise and integrate these new research findings, and identify avenues for future research.